The 18-item Swedish version of Ryff’s psychological wellbeing scale: psychometric properties based on classical test theory and item response theory - Garcia, Danilo; Kazemitabar, Maryam; Asgarabad, Mojtaba Habibi (Frontiers in Psychology, 2023)
Background: Psychological well-being is conceptualized as the full engagement and optimal performance in existential challenges of life. Our understanding of psychological well-being is important for us humans to survive, adapt, and thrive during the challenges of the 21 st century.Hence, the measurement of psychological well-being is one cornerstone for the identification and treatment of both mental illness and health promotion. In this context, Ryff (1989) operationalized psychological well-being as a six-dimensional model of human characteristics: self-acceptance, positive relations with others, environmental mastery, personal growth, autonomy, and purpose in life. Ryff's Psychological Well-Being Scale have has been developed and translated in into different versions. Here, we examine and describe the psychometric properties of the 18-item Swedish version of Ryff's Psychological Well-Being Scale using both Classical Test Theory and Item Response Theory.The data used in the present study was earlier published elsewhere and consists of 768 participants. In addition to the 18-item version of the scale, participants answered the Temporal Satisfaction with Life Scale, the Positive Affect Negative Affect Schedule, and the Background and Health Questionnaire We examined, the 18-item version's factor structure using different models and its relationship with subjective well-being, sociodemographic factors (e.g., education level, gender, age), lifestyle habits, and health issues. We also analyzed measurement invariance with regard to gender.Moreover, as an addition to the existing literature, we analyzed the properties of the 18 items using Graded Response Model.Results: Although the original six-factor structure showed a good fit, both CTT and IRT indicated that a five-factor model, without the purpose in life subscale, provided a better fit. Moreover, invariance testing showed similar measurement precision by the scale across gender. A five-factor solution is a valid and reliable measure for the assessment of psychological well-being in the general Swedish population. That being said, With some modifications, the scale might achieve enough accuracy to measure the more appropriate and correct six-dimensional theoretical framework as detailed by Ryff. Fortunately, Ryff's (1989) original version contains 20 items per subscale and should therefore act as a perfect pool of items in this endeavor.